COMMUNITY RESILIENCE AFFECTED BY THE ERUPTION OF MOUNT SEMERU IN THE ERA OF THE COVID-19 PANDEMIC - Primasari Mahardika Rahmawati; Suhari Suhari; Anggia Astuti; Musviro Musviro (UNEJ e-Proceeding, 2022)
Introduction: This study is to determine the resilience of the community affected by the eruption of Mount Semeru. The ability of the community to overcome and adapt to severe events in the face of adversity or trauma experienced in life, each community group, has different skills and capacities in responding to the disasters they face. Several variables support the level of community resilience to disasters, namely, social, economic, infrastructure, institutional, and community aspects. Resilience is often interpreted as "rising back," which reflects its nature in Latin "resilience," which means "jumping backward. Method: The design used is a descriptive method with a non-probability sampling method. Respondents amounted to 60 people. Results: The results of the WFRQ (Walsh Family Resilience Questionaire) resilience questionnaire scores showed that 60% of the people were in the category of moderate resilience. Conclusion: This study explains how the community's resilience was affected by the eruption of Mount Semeru in Lumajang Regency, East Java. Keywords: Resilience, Mountain Eruption